Analisis Dampak Kenaikan Harga Terhadap Kelangkaan Bahan Baku UMKM: Studi Kualitatif di Pabrik Tahu Marmi - Pratama, Muhammad Azdril; Simanjuntak, Tegarma Agafe; Marbun, Tesya Prysilia; Adinda, Rizki; Siahaan, Rumiris; Purba, Rakhmawati; Sarwoto, Sarwoto (STIE Bina Karya, 2024)
As a source of regional income, UMKM also play a role in reducing unemployment. Tofu making is a small business engaged in manufacturing that produces every day. To produce tofu. The raw materials needed are often scarce and experience price fluctuations. In addition to the problem of raw materials, UMKM UD Marmi which produces tofu also experiences problems in calculating production costs which are only based on estimates. The method used in this student collaborative activity seeks to help solve the problems that exist at UD Marmi in Kampung Dalam, Bajenis District, Tebing Tinggi City, engaged in the tofu factory industry. After conducting a survey and direct interviews with business owners and their workers. The input given is how to overcome the scarcity of raw material supplies and apply the calculation of production costs based on the Full Costing method, so that it is appropriate in determining the selling price of the tofu they produce.